Electrodermal activity as an index of food neophobia outside the lab - Stuldreher, Ivo V.; Van der Burg, Erik; Velut, Sebastien; Toet, Alexander; van Os, Demi E.; Hiraguchi, Haruka; Hogervorst, Maarten A.; Zandstra, Elizabeth H.; Van Erp, Jan B. F.; Brouwer, Anne-Marie (Frontiers in Neuroergonomics, 2024)
Introduction: Understanding how food neophobia affects food experience may help to shift towards sustainable diets. Previous research suggests that individuals with higher food neophobia are more aroused and attentive when observing food-related stimuli. The present study examined whether electrodermal activity (EDA), as index of arousal, relates to food neophobia outside the lab when exposed to a single piece of food.The EDA of 153 participants was analyzed as part of a larger experiment conducted at a festival. Participants completed the 10-item Food Neophobia Scale. Subsequently, they saw three lids covering three foods: a hotdog labelled as "meat", a hotdog labelled as "100% plant-based", and tofu labelled as "100% plant-based".Participants lifted the lids consecutively and the area-under-the-curve (AUC) of the skin conductance response (SCR) was captured between 20 seconds before and 20 seconds after each food reveal.We found a significant positive correlation between food neophobia and AUC of SCR during presentation of the first and second hotdog and a trend for tofu. These correlations remained significant even when only including the SCR data prior to the food reveal (i.e., an anticipatory response).The association between food neophobia and EDA indicates that food neophobic individuals are more aroused upon the presentation of food. We show for the first time that the anticipation of being presented with food already increased arousal for food neophobic individuals. These findings also indicate that EDA can be meaningfully determined using wearables outside the lab, in a relatively uncontrolled setting for single-trial analysis.